Candida Bloodstream Infection: Changing Pattern of Occurrence and Antifungal Susceptibility over 10 Years in a Tertiary Care Saudi Hospital - Nawaf Alkharashi; Sameera Aljohani; Laila Layqah; Emad Masuadi; Waleed Baharoon; Hamdan AL-Jahdali; Salim Baharoon (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Candida has emerged as one of the most important pathogens that cause bloodstream infection (BSI).Understanding the current Candida BSI trends, the dominant species causing disease and the mortality associated with this infection are crucial to optimize therapeutic and prophylaxis measures. Objectives. To study the epidemiology and to evaluate the risk factors, prognostic factors, and mortality associated with candidemia and to compare these findings with previously published studies from Saudi Arabia. Design. A retrospective medical record review. Setting. Tertiary hospital in Riyadh. Patients and Methods. The analysis included all cases of Candida blood stream infection who are >18 years old over the period from 2013 to 2018. Continuous variables were compared using the parametric T-test while categorical variables were compared using the Chi-squared test. Main Outcome Measure. Incidence, resistance, and hospital outcomes in Candida blood stream infection. Sample Size. 324 patients. Results. Three hundred and twenty-four episodes of Candida blood stream infections were identified. Median age of patients was 49.7 SD ± 28.1 years, and 53% of patients were males. More than half of the patients had an underlying disease involving the abdomen or laparotomy, 78% had an indwelling intravenous catheter, and 62% had suffered a bacterial infection within 2 weeks prior to candidemia. Candida albicans represents 33% of all isolates with decreasing trend overtime. There was an increase in the number of nonalbicans Candida overtime with Candida tropicalis in the lead (20%). Use of broad spectrum antibiotics (82%), prior ICU admission (60%) and use of central venous catheters (58%) were the most prevalent predisposing factors of candidemia. Azole resistance was variable overtime. Resistance to caspofungin remained very low (1.9%). Fourteen days crude mortality was 37% for ICU patients and 26.7% in non-ICU patients, while hospital crude mortality was 64.4% and 46.7%, respectively. Conclusion. There is an increasing trend of nonalbicans Candida blood stream infection. Fluconazole resistance remained low to C. albicans. Most isolates remain susceptible to caspofungin, voriconazole, and amphotericin B. Candida bloodstream infection is associated with high 14-day hospital mortality.